2022
DOI: 10.3390/jcm11051304
|View full text |Cite
|
Sign up to set email alerts
|

Locomotive Syndrome and Lumbar Spine Disease: A Systematic Review

Abstract: Locomotive syndrome (LS) is defined based on the Loco-Check, 25-question Geriatric Locomotive Function Scale (GLFS-25), 5-question Geriatric Locomotive Function Scale (GLFS-5), Stand-Up Test, Two-Step Test, or a total assessment (i.e., positive for one or more of the GLFS-25, Stand-Up Test, and Two-Step Test). Lumbar spine disease has been reported to be one of the most common musculoskeletal disorders leading to LS. We therefore conducted a systematic review via PubMed, Google Scholar, Cochrane Library, Web o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The Locomo Age of patients with sarcopenia was higher than those without sarcopenia. Previous reports indicated that osteoarthritis, 19,20 spinal disorders, 19,21,22 and sarcopenia [23][24][25][26] are closely related to LS severity. Therefore, these comorbidities increase Locomo Age and hence, the patients with these conditions should be treated to decrease their Locomo Age.…”
Section: Discussionmentioning
confidence: 97%
“…The Locomo Age of patients with sarcopenia was higher than those without sarcopenia. Previous reports indicated that osteoarthritis, 19,20 spinal disorders, 19,21,22 and sarcopenia [23][24][25][26] are closely related to LS severity. Therefore, these comorbidities increase Locomo Age and hence, the patients with these conditions should be treated to decrease their Locomo Age.…”
Section: Discussionmentioning
confidence: 97%
“…Particularly, sagittal spinopelvic malalignment was associated with LS. Therefore, sagittal spinopelvic malalignment may be a trigger for suspected LS 49. The spinal inclination angle was observed as the most relevant for LS among the sagittal spinopelvic parameters, and a spinal inclination angle of ≥6° has a sensitivity of 52% and specificity of 87% for LS category 31…”
Section: Discussionmentioning
confidence: 97%
“…The Newcastle-Ottawa Scale adapted for cross-sectional studies 49 was used to make a quality assessment of the included studies.…”
Section: Methodsmentioning
confidence: 99%
“…It is scored by normalizing the maximal length of two steps by the height. Two-Step Test scores < 0.9, <1.1, <1.3, and ≥1.3 points correspond to LS-3, LS-2, LS-1, and non-LS [ 7 ].…”
Section: Methodsmentioning
confidence: 99%